Analisis Kuat Tekan Dan Kuat Tarik Belah Beton Dengan Menggunakan Cangkang Kepiting Dan Cangkang Kerang Sebagai Pengganti Parsial Semen - Paraktuk, Azer Kalak; Mallawangeng, Tamrin; Yuniarto, Eka (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The use of concrete materials in the world of construction has become the main choice because of its strength and durability. However, the use of concrete also has negative impacts on the environment, such as carbon dioxide emissions and the use of large amounts of energy. Therefore, using organic waste such as crab shells and oyster shells can help reduce waste and promote recycling practices. In this research, a normal concrete compressive strength design of 25 MPa was used with the aim of research to obtain the effect of using crab shells and clam shells as a partial replacement for cement. The mixing method is carried out by partially replacing cement with crab shell powder and oyster shells as much as 4%, 8% and 12%, by carrying out compressive and tensile strength tests of the concrete. This research shows that partial replacement of cement with crab shells and clam shells for concrete as a whole causes a decrease in compressive and tensile strength. However, the use of oyster shells as a substitute for cement at an addition of 4% produces concrete compressive strength and split tensile strength that is slightly higher compared to normal concrete targets and the use of crab shells at the same percentage.